Media Arabic : a coursebook for reading Arabic news = Lughat wasa'il al-i'lam al-'Arabiyah - Elgibali, Alaa; Korica, Nevenka (Cairo ; New York : The American University in Cairo Press, 2007)
'In light of the rapidly growing number of people studying Arabic - in academia, governments, NGOs, and business - Media Arabic is a unique and timely learning tool for anyone looking to access news information from the Arab world first hand. Media Arabic introduces the language of newspapers, magazines, and Internet news sites to intermediate- and advanced-level students of Modern Standard Arabic. Using this coursebook, students will be able to master core vocabulary and structures typical of front-page news, recognize various methods of coverage, distinguish fact from opinion, detect bias, and read critically in Arabic.''The book enables students to read extended texts with greater accuracy and speed by focusing on the relationships among meaning, linguistic form, and discourse markers. Activities include pre-reading discussions as well as extensive practice on vocabulary use in context, organizing information, skimming, scanning, critical reading, and analyzing content.'--BOOK JACKET.
Arabic and English.
Keywords: Arabic language -- Textbooks for foreign speakers -- English; Arabic language -- Composition and exercises; Arabic language -- Business Arabic; Mass media and language -- Arab countries